PENERAPAN PENDEKATAN PEMECAHAN MASALAH MENURUT POLYA MATERI PERSEGI DAN PERSEGI PANJANG UNTUK MENINGKATKAN HASIL BELAJAR SISWAKELAS VII B SMP NEGERI 10 JEMBER TAHUN AJARAN 2012/2013 - Pramita N, Wirdah; Pambudi, Didik Sugeng; Kristiana, Arika Indah (Kadikma, 2014)
Abstract.In general, mathematics learning at schools is still a teacher centered, so the students become less active in teaching-learning process. Beside that, the students are also never given a problem-solving work done in groups. It causes the students become passive and just listen to the teacher’s explanation. It makes the students bored and invites difficulties in learning mathematics. It also causes the low score of the student learningachievement. Therefore, it needs a development of learning by applying a problem-solving approach as Polya says about square and rectangular objects to improve the student learning achievement of class VII B in SMP Negeri 10 Jember 2012/2013 academic year. Polya says, in a problem-solving approach, there are four steps, include: understanding the problem, devising a plan, carring out the plan, and looking back. Based on the research, the application of problem-solving approach, as Polya underlines, is effective to improve the student learning achievement in square and rectangularobjects. It is proved by the result of student learning achievement, which is from 58,33% to 88,89%. Key Words:Polya’s problem solving approach, square and rectangular, student learning achievement.